Roles of Krüppel-like factor 4 in oesophageal epithelial cells in Barrett's epithelium development. Issue 5 (30th December 2010) - Kazumori, Hideaki; Ishihara, Shunji; Takahashi, Yoshiko; Amano, Yuji; Kinoshita, Yoshikazu
Abstract : Objectives: The mechanism of transformation to intestinal metaplasia in Barrett's oesophagus has not been clarified. We previously reported that bile acids activate the Cdx2 promoter via nuclear factor kappa B (NF-κB) and stimulate production of Cdx2 protein in oesophageal keratinocytes, resulting in production of intestinal-type mucin. Krüppel-like factor 4 (KLF4) is an important transcription factor in the development of intestinal mucosa and has similar functions as Cdx2. In the present study, we investigated the direct effects of bile acids on KLF4 expression as well as the precise mechanisms of expression in cultured oesophageal squamous epithelial cells. Methods: We investigated the expression of KLF4 in rat and human Barrett's epithelium specimens, while the response of that expression to bile acids was studied using a KLF4 promoter luciferase assay. In addition, oesophageal squamous epithelial cells were transfected with a KLF4 expression vector, after which their possible transformation into intestinal-type epithelial cells was investigated. Results: In both rat and human tissues, Barrett's epithelium strongly expressed KLF4. Furthermore, a bile acids mixture increased KLF4 promoter activity, and mRNA and protein expression in oesophageal epithelial cells. Results from mutation analysis of the KLF4 promoter suggested that the NF-κB binding site is responsible for bile acid-induced activation of the KLF4 promoter. In addition, KLF4 and Cdx2 stimulated each other by directly binding to the promoter of the other, while transfection of the KLF4 expression vector in oesophageal epithelial cells induced production of MUC2 protein. Conclusion: Bile acid-induced sequential expression of KLF4 followed by MUC2 production may have an important role in the development of Barrett's epithelium.